Nonsurgical Medical Penile Girth Augmentation: A Retrospective Study of Psychological and Psychosexual Outcomes. (8th May 2018) - Sharp, Gemma; Oates, Jayson
Abstract: Background: Although interest in penile augmentation procedures is increasing, there is a significant lack of research into the psychological and psychosexual outcomes of these procedures. Objectives: To investigate the psychological and psychosexual outcomes of nonsurgical medical penile girth augmentation. Methods: This retrospective study involved a mixed method approach. Twenty-five men who had undergone a nonsurgical medical penile girth augmentation between 1 and 12 months prior (mean, 6.6 months) completed an online questionnaire containing measures of procedure motivation, procedure satisfaction, genital self-image, penile-focused body dysmorphic disorder symptoms, self-esteem, and sexual relationship satisfaction. Six of these men elected to complete in-depth one-to-one semi-structured phone interviews to further explore the psychological impacts of the procedure. Results: In the online questionnaire, most men were satisfied with their penile size, appearance, and function after penile girth augmentation. The men also reported statistically significant improvements in their genital self-image ( P < 0.001) and self-esteem ( P = 0.008), and a reduction in penile-focused body dysmorphic disorder symptoms ( P = 0.002) at the time of completing the questionnaire compared to recalled pre-procedural levels. The in-depth interviews yielded 3 themes surrounding penile augmentation outcomes: (1) high satisfaction with increased penis girth; (2) increased self-confidence, particularly in situations in which the penis would be seen, such as a locker room; and (3) increased sexual confidence, but some mixed impacts on sexual relationships. Conclusions: Most men appear to be satisfied with their nonsurgical medical penile girth augmentation results, and they also seem to experience improvements in their overall self-esteem. Level of Evidence: 4: